Niche and Interspecific Association of Dominant Phytoplankton Species during Winter in Eight Estuaries of Pearl River - HE Rui; LI Qingfeng; PENG Songyao (Renmin Zhujiang)
To understand the niche and interspecific association of the dominant phytoplankton species during winter in the Pearl River estuaries, this paper selects eight Pearl River estuaries as the study area. Phytoplankton and environmental factors were detected in eight Pearl River estuaries in December 2019. The dominance value, niche width, niche overlap, variance ratio method, chi-squared test (χ2), and CCA are utilized to analyze the niche and interspecific association with respect to the dominant phytoplankton species. The results are as follows.① 54 species belonging to 6 phyla are identified, of which 7 species from 30 genera are the dominant species.② The niche width of the dominant species and the niche overlap values vary greatly among species pairs. Aulacoseira granulata has strong adaptability to the aquatic environment and exhibits a wide range of ecological adaptability. The niche overlap value of Skeletonema costatum is low, and interspecific competition is weak. ③ The phytoplankton of the Pearl River Estuary is generally in an early stage of succession and there is a trend of positive succession. The linkage community in the Pearl between species is not strong and the interspecific relationship is loose. The dominant phytoplankton species have not yet reached a relative dynamic equilibrium among themselves and between the dominant species and the environment, and the dominant species are in the stage of development. ④Ammonia nitrogen, total organic carbon (TOC), and turbidity are the main environmental factors affecting the distribution and ecological position of the dominant phytoplankton species in the eight Pearl River estuaries.